Kant, equal opportunities and merit - Baiasu Sorin (Belgrade Philosophical Annual, 2024)
The aim of this paper is very ambitious as it proposes to argue for a change of perspective in our reading of some aspects of Kant's political philosophy and potentially of his practical (moral and political) thought more generally. In particular, the paper will argue that, beyond the well-known and influential Socialist, Republican, Liberal, Consequentialist and Libertarian readings of Kant, it would be promising to consider an original Desert-sensitive reading. I will focus on a relatively recent and influential version of the Republican reading, and I will evaluate both its interpretative and philosophical cogency; indirectly, I will argue for a better, Desert-sensitive Reading of Kant's account of equal opportunities.